The Effectiveness of Mathematics Learning Using Adobe Flash Media on Student Learning Outcomes - Novitasari, Nadhea; Lismareni, Neni; Susanti, Novi (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2024)
Students in the era of school digitalization very much need numeracy skills. Numeracy skills are related to solving a problem. Adobe Flash media is suitable for solving a problem with the help of interactive animated videos. This study aimed to determine the effectiveness of mathematics learners using Adobe Flash Media, which was assisted by interactive animated videos on students' numeracy skills. The research method used is quantitative in the form of a true experiment. The sample in this study were students in grades VIII8 and VIII7, who were selected randomly. The data collection techniques used were documentation and tests. The data analysis techniques used were normality tests, homogeneity tests and independent sample tests. The results of the study showed that the t count value > t table where t count = 7.602 and t table = 1.6905. This means that there is a significant difference in the average numeracy ability of students between the experimental group and the control group.